2018
DOI: 10.1002/eji.201747463
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected involvement of IL‐13 signalling via a STAT6 independent mechanism during murine IgG2a development following viral vaccination

Abstract: In this study, recombinant pox viral vaccination was shown to induce highly elevated IgG2a and low IgG1 antibody expression in mice lacking IL-4 or STAT6, whilst IL-13 mice exhibited elevated IgG1, but very low IgG2a. These findings revealed that IL-13 and IL-4 differentially regulated antibody development. To understand this further, when STAT6 mice were given a vaccine co-expressing IL-13Rα2 that temporarily sequestered IL-13, significantly reduced IgG2a expression, was detected. These findings for the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…rMVA or rVV boost vaccination strategy) can induce high avidity/poly-functional mucosal and systemic T cells with better protective efficacy 15,17 , which was associated with elevated cDC recruitment 17,19 . These studies also showed that IL-13 was necessary for effective antibody differentiation 15 , which was regulated via a STAT6 independent pathway 28 . When trying to unravel how IL-13 modulated these different vaccine-specific outcomes current study revealed that, i) under low IL-13 conditions/rFPV vaccination (which induced low IL-13 at the lung mucosa), IL-13Rα2 expression was up-regulated on DC; ii) under low IL-13/STAT3 inhibition IL-13Rα2 expression was up-regulated whilst TGF-β1 was down-regulated on lung DCs, as opposed to STAT6 inhibition; iii) Moreover, up-regulation of phosphorylated STAT3 and TGF-β1 was detected on STAT6 −/− cDCs post rFPV vaccination.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…rMVA or rVV boost vaccination strategy) can induce high avidity/poly-functional mucosal and systemic T cells with better protective efficacy 15,17 , which was associated with elevated cDC recruitment 17,19 . These studies also showed that IL-13 was necessary for effective antibody differentiation 15 , which was regulated via a STAT6 independent pathway 28 . When trying to unravel how IL-13 modulated these different vaccine-specific outcomes current study revealed that, i) under low IL-13 conditions/rFPV vaccination (which induced low IL-13 at the lung mucosa), IL-13Rα2 expression was up-regulated on DC; ii) under low IL-13/STAT3 inhibition IL-13Rα2 expression was up-regulated whilst TGF-β1 was down-regulated on lung DCs, as opposed to STAT6 inhibition; iii) Moreover, up-regulation of phosphorylated STAT3 and TGF-β1 was detected on STAT6 −/− cDCs post rFPV vaccination.…”
Section: Discussionmentioning
confidence: 93%
“…Studies have shown that STAT6 and STAT3 can be differentially regulated, according to the state of viral infection/vaccination. Specifically, in the context of viral vector-based vaccination whilst IL-13/STAT6 signalling has been shown to dampen effective antiviral immunity 13,28 , however in acute and primary viral infections, it has shown to improve antiviral immunity 50,51 . This study showed that viral vector induced IL-13 "level" in the cell milieu significantly altered the STAT3/STAT6 equilibrium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations